Pengaruh Wealth, Intergovernmental Revenue, Leverage dan Opini Audit BPK Terhadap Kinerja Keuangan Pemerintah Daerah (Studi Kasus Pada Pemerintah Kota Lhokseumawe) - Dy Ilham Satria; Heny Puspita Sari (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2018)
This research aims to analyze the influence of wealth, intergovernmental revenue, leverage, and audit opinion of BPK on local government financial performance with a case study on Lhokseumawe city government in 2011-2015. The data used in this study is secondary data obtained from the office of BPKD of Lhokseumawe city government. Data analysis method in this research is through documentation data obtained from Local Government Financial Report (LKPD), document data in the Budget Realization Report, Balance Sheet, Opinion Audit BPK of Lhokseumawe Government during 2011-2015. The results of this study indicate that wealth and leverage have no effect on the financial performance of local government of Lhokseumawe, while the intergovernmental revenue and BPK Audit influence on the performance of Lhokseumawe city government, and the measurement of financial performance through efficiency ratio of Lhokseumawe city is less efficient in running the government through the effectiveness ratio of Lhokseumawe city is quite effective in running the government.